Exploring Santoon's Customers' Preferences That Affect Their Purchase Decision For Buying Fashion Products - Wibowo, Amira Luthfiyya (Integrasi Sains Media, 2024)
There is a significant shift towards online shopping in the digital era, particularly within the fashion industry. Despite this trend, Santoon, a clothing brand in Indonesia, faces challenges with online sales being considerably lower than offline sales, even though many of its customers and target market prefer purchasing fashion products online. This study aims to identify the preferences of Santoon's customers that impact their decision-making process when buying fashion products. Adopting a qualitative approach, the research utilizes semi-structured interviews to gather in-depth insights. A non-probability purposive sampling technique focused on Santoon's past customers and target market. The study reveals that design, quality, and sizing are the primary factors influencing customers' preferences for fashion products. Additionally, detailed product descriptions and customer reviews are crucial in shaping online shopping preferences. Although customers often visit offline stores to see and sample products, the final purchase decision is frequently made online. The findings underscore the importance of enhancing online product descriptions and leveraging customer reviews to build trust. Integrating online and offline shopping experiences is essential to cater to hybrid customer behaviour. Recommendations for Santoon include improving the detail and accuracy of online product descriptions, utilizing customer reviews to foster trust, and merging online and offline shopping experiences. Furthermore, optimizing Instagram marketing by posting content related to the daily use of Santoon's products is advised, given the significant overlap between the brand's target market and Indonesian Instagram users.